Mechanism and optimum pressure for sliding-mode nanogenerator - Yun Hang; He Ren (Polish Journal of Chemical Technology, 2023)
Triboelectric nanogenerator has extensive applicability because of its capability of harvesting mechanical energy and flexible working modes. To research the optimum pressure and improve the recovered energy of the sliding-mode triboelectric nanogenerator, a contact model of the Al/PTFE tribo-pair is studied by ab initio calculation and finite element simulation. The F-atom of PTFE is proved to be the electron accepter and the charges transferred can be predicted by Bader charge analysis. The mathematical relation between interfacial distance, charges transferred and contact pressure can be fitted. By Gauss’s law, the electric field is simulated and the regeneration energy of the sliding-mode triboelectric nanogenerator can be evaluated by the total electric energy and friction loss. Finally, an optimum pressure can be set to the upper or lower limit of working pressure corresponding to larger recovered energy. And less friction coefficient and larger contact area are also effective methods for recovering energy.